Criminal Offense Of Narcotics Abuse Of Children According To The Law Of Ri No. 35 Of 2009 Concerning Narcotics Case Study of Decision Number XX/Pid.Sus-Anak/2022/PN Cbi. - Saputra, Pahlan; Hilman, Didi; Lestari, Nisa (JURNAL MAHASISWA YUSTISI, 2025)
Drug abuse in Indonesia is currently increasing and difficult to control. Drug trafficking is not only in big cities but has reached villages, involving not only therapeutic adults but also children. The involvement of children in drug trafficking is a very serious and complex matter. Furthermore, children involved with drugs can be referred to as children in conflict with the law or children who commit criminal offenses or juvenile delinquency. Narcotics are substances or drugs derived from plants or non-plants, both synthetic and semi-synthetic. These substances cause a decrease or change in consciousness, eliminate taste, reduce to eliminate pain, and can cause addictive dependence disorders. Children in conflict with the law are caused by child delinquency. Therefore, children as part of the younger generation are the successor to the ideals of the nation's struggle and are human resources for future national development. This research uses a normative juridical method based on data obtained through legislation, scientific works, and field surveys, where the data that has been obtained is analyzed through the use of qualitative methods. The legal regulation of children as drug abusers according to criminal law is the imposition of articles on children the same as adults, namely Article 114 paragraph (1) and paragraph (2) of Law Number 35 of 2009 concerning Narcotics, only the difference lies in the application of sanctions that are lower than adults who must be guided by Article 81 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, among others: The maximum imprisonment that can be imposed on children is 1/2 (one-half) of the maximum imprisonment for adults. Criminal law protection for child drug abusers has used diversion through a restorative justice approach. Case No. XX/Pid.Sus-Anak/2022/PN Cbi. The imposition of imprisonment to children can have a prolonged negative impact which is counter-productive when viewed from the main objective of the punishment itself. The purpose of punishment, especially for children, in reality cannot be fulfilled by imposing imprisonment on children. The placement of juvenile offenders in correctional institutions for adults makes children not get their rights optimally because the coaching program is more intended for adults so that the purpose of punishment cannot be achieved.